Determination of Relationship and Path Co-efficient between Pod Yield and Yield Component Traits of Groundnut Cultivars - Thakur, SB; Ghimire, SK; Chaudhary, NK; Shrestha, SM; Mishra, B (Nepal Journal of Science and Technology, 2014)
Twenty - five groundnut genotypes, obtained from National Oilseed Research Program (NORP), Nawalpur, Nepal along with local checks (B -4, Baidehi, Rajshree and Jayanti) were used to study correlation and path co-efficient among pod yield and yield component traits in groundnut. The pod yield ha-1 showed highly significant and positive association with days to maturity, sound matured kernel (SMK)%, pod length, pod width and kernel length but the highly significant and negative association was shown with days to flowering, pod plant-1, shoots length, shelling % and specific leaf area. Partitioning the total yield contributions into individual and combined effect showed that days to maturity, root length, pod width, pod length and kernel length made individual high positive direct contribution to pod yield ha-1.Days to flowering, shoot length, shelling %, SMK% and100 kernel weights had direct negative contribution with pod yield ha-1. Therefore, days to maturity, root length, pod width, pod length and kernel length were identified to be the important traits which could be used in selection for yield. DOI: http://dx.doi.org/10.3126/njst.v14i2.10409 Nepal Journal of Science and Technology Vol. 14, No. 2 (2013) 1-8